ANALYSIS OF THE EXPORT CAPACITY AND COMPETITIVENESS OF ENTERPRISES (Marketing Journal, 2025)
The article examines the approaches of foreign researchers to the concept of export potential of enterprises, the components of export potential and indicators of their competitiveness, as well as the results of studies of factors influencing the export potential of an enterprise.
Keywords: export potential; regional export potential; enterprise export potential; competitive advantage; competitive products; financial resources; labor resources; distribution and logistics